Clinical Profile and Upper Gastrointestinal Endoscopic Findings of Patients Presenting with Liver Cirrhosis with Portal Hypertension - Chaudhary, Shatdal; Jaiswal, Niraj Kumar; Shahi, Aakash; Chhetri, Pradip (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Liver cirrhosis is a common problem faced by physicians worldwide and is also responsible for 11th most common cause of death globally. Data regarding prevalence of esophageal varices and other upper gastrointestinal changes in patients with liver cirrhosis is scare in Nepal. So this study was carried out to find clinical profile and upper gastrointestinal endoscopic findings of patients presenting with liver cirrhosis with portal hypertension.Methods: This was a cross-sectional observational hospital based study conducted in the department of internal medicine and endoscopy unit of the Universal College of Medical Sciences, Bhairahawa, Nepal. The study was done from 21 February 2019 to 20 November 2019 in the patients presented with liver cirrhosis with portal hypertension. Sample size of 80±10 was calculated based on the statistics of previous data. The upper gastrointestinal endoscopy was done in all the patients. The data was collected using the predesigned pro-forma.Results: Total 89 patients with liver cirrhosis were enrolled with mean age of 51.84±12.26 years and male: female ratio of 3.68:1. As per Child Pugh classification (CTP) 45 patients (51%) were in Class C, 33 patients (37%) were in Class B and 11 patients (12%) were in Class A. Esophageal varices were present in 51 (57.3%) patients. According to Westaby classification grade I esophageal varices were seen in 17 (19.1%), grade II esophageal varices were seen in 26 (29.2%), grade III esophageal varices were seen in 8 (8.9%) patients. Portal hypertensive gastropathy (PHG) was seen in 64 (71%) patients. The association between esophageal varices and PHG grade was found statistically significant (P=